Indicadores para el seguimiento y control de prácticas anticompetitivas en el mercado eléctrico colombiano (2018)
This paper proposes a methodology for the development and implementation of two index, impact index and incentive index, to evaluate the behavior of agents in the wholesale energy market in Colombia. For its formulation, statistical analyzes and modeling with neural networks were performed. Case studies were simulated to achieved economic and behavior analysis of these indexes. The proposed indexes are useful to manage and capture strategic behavior of agents and for its implementation it is recommended that the monitoring and control entities have a programming platform, in the case of input information there is a free access database.